Novel, chimpanzee serotype 68-based adenoviral vaccine carrier for induction of antibodies to a transgene product. - Xiang, Z; Gao, G; Reyes-Sandoval, A; Cohen, C; Li, Y; Bergelson, J; Wilson, J; Ertl, H (2002)
An E1-deletion-containing adenoviral recombinant based on the chimpanzee serotype 68 (AdC68) was developed to express the rabies virus glycoprotein. Mice immunized with this construct (AdC68rab.gp) developed antibodies to rabies virus and remained resistant to challenge with an otherwise lethal dose of rabies virus. In naïve mice immunized intranasally, the rabies virus-specific antibody responses elicited by AdC68rab.gp were comparable with regard to both titers and isotype profiles to those induced by an adenoviral recombinant based on human serotype 5 (Adhu5) expressing the same transgene product. In contrast, subcutaneous immunization with the AdC68rab.gp vaccine resulted in markedly lower antibody responses to the rabies virus glycoprotein than the corresponding Adhu5 vaccine. Antibodies from AdC68rab.gp-immunized mice were strongly biased towards the immunoglobulin G2a isotype. The antibody response to the rabies virus glycoprotein presented by Adhu5rab.gp was severely compromised in animals preexposed to the homologous adenovirus. In contrast, the rabies virus-specific antibody response to the AdC68rab.gp vaccine was at most marginally affected by preexisting immunity to common human adenovirus serotypes, such as 2, 4, 5, 7, and 12. This novel vaccine carrier thus offers a distinct advantage over adenoviral vaccines based on common human serotypes.